Return to sport in a COVID-10 environment - Hughes, D.; Mooney, M.; Perera, N.; Saw, R. (Sport Health, 2020)
Australian sporting organisations are attempting to function under what are arguably, the most difficult conditions in history. This piece reflects on articles written around this topic over the past six months and the stunning rapid acceleration of cases diagnosed around the world and what that means for sport and its return.